THE GROWING ENERGY CRISIS - Mathew, Thomas (SCHOOL SCIENCE, 2012)
The inhabitants of Delhi will remember the summer of 1973 for the fickleness of the city’s power supply. Yet it served as an uncomfortable reminder to the citizens of the capital, of the acute power famine that is now plaguing the whole of the country. Apart from the inconvenience caused to the public, the industrial and agricultural sectors of our economy are hard hit, since for them power is an essential requirement. Industry as a whole may lose up to ` 30 crore a month. Dr K.L. Rao has estimated that the loss to the country from power cuts is of the order of `1000 crore. And on and on runs this disheartening story.